WHAT SHOULD INTELLIGENCE PRIORITIES BE GIVEN THE STATE OF HEGEMONIC INSTABILITY? - Loch K. Johnson (The Journal of Intelligence, Conflict and Warfare, 2024)
On November 15, 2023, Dr. Loch K. Johnson, Regents Professor Emeritus of Public and International Affairs at the University of Georgia, presented What Should Intelligence Priorities Be Given The State of Hegemonic Instability? for this year’s West Coast Security Conference. The presentation was followed by a question-and-answer period with questions from the audience and CASIS Vancouver executives. The key points discussed were the history of US intelligence prioritization, the need for increased attention towards universal threats, and the need for open societies to share intelligence tasking and findings with each other.